ALGORITMA FUZZY GOAL PROGRAMMING UNTUK MASALAH PEMROGRAMAN BILEVEL MULTIOBJEKTIF - Syarifah Inayati (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2018)
Bilevel multiobjective programming problems are mathematical programming that solves the problem of planning with two decision makers (DM) in two level or hierarchical organization with the objective function of each organization can be more than one. In this paper, we discussed the special case of this problem with single decision maker at the upper level and multiple decision makers at the lower level. This problem can be solved using fuzzy goal programming (FGP) approach. In this approach, the membership function for the defined fuzzy goals of all objective functions of DMs at the two levels was developed first in the model formulation of the problem. Thus the membership function for vector of fuzzy goals of the decision variables controlled by the leader. Then FGP approach requires the leader to set goals for each objective that he/she wishes to attain. A preferred solution is then defined for minimizes the deviations from the set of goals. Numerical example is provided to illustrate the approach.